Reaction to Modernity and Westernization in Lafcadio Hearn’s Glimpses of Unfamiliar Japan and In Ghostly Japan - Estherina, Janet (Lingua Susastra, 2025)
This paper analyzed the works of Lafcadio Hearn, Glimpses of Unfamiliar Japan and In Ghostly Japan, under the lens of Westernization and modernization of Japan at that time. Hearn was a writer who occupied a unique position in Japan. Despite his foreign origin, he, unlike the other Westerners at that time, showed a great deal of respect towards Japanese culture and even chose to live in the Japanese way. Hearn’s works showed a fascination with Japanese folk tales and traditional way of life, and also concerns over modernization and Westernization. However, Hearn also believed that Japan was able to maintain its unique character in the face of Westernization. Hearn’s love for the folk tales and traditional culture of Japan puts him with the folk Decadent who latch on to folk traditions in response to modernity. Both Glimpses and In Ghostly Japan showed Hearn’s great interest towards traditional Japanese culture which is the characteristic of folk Decadence, although Glimpses showed a greater leaning toward Hearn’s conservatism.